A DESCRIPTION OF KNOWLEDGE, ATTITUDES, AND BEHAVIOUR REGARDING BREAST SELF-EXAMINATION AMONG ADOLESCENT GIRLS IN NAIKOLAN SUBDISTRICT, KUPANG CITY - Maria Magdalena Dwi Wahyuni; Wiliam Jordan Takesan; Aletha Anasthasya Litelnoni; Santaliana Albania Pakaer; Theresia Melania Wonga; Arias Umbu Amas (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2026)
Breast cancer is the top cause of illness and death among women globally. Breast Self-Examination (BSE) is a method for early detection that can be done independently; yet, its practice among teenage girls is still not ideal. This research seeks to outline the understanding, perceptions, and practices related to BSE among teenage girls in Naikolan Village, Maulafa Sub-district, Kupang City. The research utilized a quantitative descriptive approach through a quick survey method and a two-phase cluster random sampling strategy, with 210 female adolescent participants aged 15–24 years. Data were gathered through interviews utilizing a structured questionnaire entered through the Epi Collect 5 application. The results indicated that most respondents (76.19%) lacked adequate knowledge of BSE, especially concerning when to perform the examination and signs of breast irregularities. A total of 56.19% of participants showed negative sentiments, particularly concerning their faith in the long-term advantages of BSE. At the same time, 73.81% of participants showed behavior deemed as supportive of BSE. These results reveal a disparity between awareness and beliefs versus actions, highlighting the necessity for organized and ongoing health education initiatives to bolster the cognitive and emotional bases of adolescent girls in conducting self-examinations for early breast cancer detection.